Религия в системе образования Республики Беларусь - Дьяченко, О. В. (НТУ "ХПИ", 2012)
Приведена информация о характере взаимодействия церкви и системы образования Республики Беларусь в духовном воспитании молодежи. В то же время показано, что государственная политика основывается на принципе светского характера образования. Раскрыты особенности взаимодействия с религиозными организациями в условиях поликонфессиональности.

Information about the character of cooperation of church and system of formation of the Republic Byelorussia in spiritual education of young people is resulted. It is shown at the same time, that a state policy is based on principle of society character of education. The features of cooperation with religious organizations in the polyconfessional conditions are exposed.
Religion in the system of formation of the Republic Byelorussia
Keywords: церковь; воспитание духовное; образование светское; политика государственная; поликонфессиональность